Women and Covid19: How the Italian Government Task Force Fostered Gender Equity - Camussi, E.; Rella, R.; Grigis, P.; Sassi, C.; Annovazzi, C. (Frontiers in Human Dynamics, 2021)
Over the last decades, the social context has been characterized by uncertainty, complexity, and inequalities, with significant impacts on people, groups, and communities. Covid-19 Pandemic has accentuated social discriminations, as inequalities affecting women (WHO, 2020), with repercussions on general income, health, education (Office for National Statistics, 2021) that have been exhausting people, the economic system, and the welfare state (Antonicelli et al., 2020). To cope with these difficulties, on April 10 2020 the Italian Prime Minister appointed a Task Force of 17 experts with scientific and applicative skills in social and economic fields. Within a short time, the Task Force aimed at identifying practical solutions priming the relaunch of the country. Given the women’s central role in the country’s social and economic development, in the final version of the Task Force plan, Gender Equality was indicated as the third - strategic and innovative - axis, together with Digitization and Green Economy. Its rationale was to promote gender equality in every action, with an allocation of dedicated economic resources. Specifically, the Task Force’s Working Group named “Individuals, Families, and Society” proposed specific initiatives aimed at recognizing and bridging the gender gaps in the various areas, and measures to support vulnerable people. This contribution will focus on the central role that the Task Force has played in encouraging systematic attention to women, considering their needs and the social-economic impacts on their choices and well-being. It will illustrate the Task Force’s internal dynamics (there were 4 women out of 17 people, then increased), the process of inclusion of different perspectives, both gender and multidisciplinary, and the practices suggested for the post-pandemic rebuilding. The final goal will be to show the inability to promote innovation, resilience and sustainability, without working with and for the community. As shown by the Italian Task Force, an innovative change must consider a multiplicity of perspectives that reflects the complexity of reality, even in the political and decision-making debate. Therefore, it’s central to build multidisciplinary teams that include various professionals from the social sectors, as Social Psychology, Sociology, Pedagogy, Political Philosophy, Demography, and Social Statistics, both women and men.